The Scope and Limits of Protection for Distinctive Signs against the Community Design : The Application and Implications of Art. 25 (1) (e) of the Community Designs Regulation - Kolasa, Magdalena (Nomos Verlagsgesellschaft mbH & Co. KG, 2012)
This book addresses the application and the implications of Art. 25(1)(e) CDR - the basis for invalidation of a Community design on the basis of infringement of a prior distinctive sign. This potentially attractive provision, allowing for an invalidation with reference to various legal provisions, results to date in a lower number of invalidations than Art. 25(1)(b) CDR - the other basis for invalidation available for the owners of distinctive signs.
English
Keywords: Markenrecht; Urheberrecht / Gewerblicher Rechtsschutz und Medienrecht; Gewerblicher Rechtsschutz